Effects of Space Weather on Technology Infrastructure - Daglis, Ioannis A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
The highly variable conditions in the Earth-related space environment, including the Sun, the interplanetary medium and the coupled magnetosphere-ionosphere-atmosphere system, are collectively known as space weather. In the recent past we have experienced that space weather influences the performance and reliability of space- and ground-based technological systems. Although several technological impacts of space weather had been known for some time, it was not before the 1990s that their significance increased dramatically and their severity became apparent. Furthermore, an increasing susceptibility of spacecraft systems to space weather disturbances has been noticed, presumably due to "softer" designs of electronic components, reduction in subsystem sizes, and increases in performance demands. On the ground side, previously unidentified effects of space weather on power grids have been discovered recently. The 17 chapters of this book provide an update of the existing knowledge on dynamic physical processes at the Sun, the interplanetary space and the geospace, as well as thorough reviews of the major mechanisms in which space weather disturbances influence technological systems. The book moreover reports recent advances in monitoring and predicting space weather and its impacts on technology systems and introduces new tools and methods for accurate predictions of space weather disturbances. Target audience: researchers, teachers and students in space physics and space-related engineering, electric power and space communication technology community, astronomers, non-specialist physicists and engineers.
Specifying and Forecasting Space Weather Threats to Human Technology -- Geospace storm dynamics -- Structure and Dynamics of the Outer Radiation Belt -- The Ion Radiation Belts: Experiments and Models -- Outlook on Space Weather Effects on Spacecraft -- Space Weather Effects on SOHO and its Space Weather Warning Capabilities -- Prevention of Spacecraft Anomalies - The Role of Space Climate and Space Weather Models -- The relation of high- and low-orbit satellite anomalies to different geophysical parameters -- Simulation of Space Radiation Effects in Microelectronic Parts -- The Effects of Space Weather on Radio Systems -- Effects of Solar Radio Bursts on Wireless Systems -- Space Weather Effects on Aircraft Operations -- Ground Effects of Space Weather -- Space Weather and the Vulnerability of Electric Power Grids -- Space Weather Effects on Power Transmission Systems: The Cases of Hydro-Québec and Transpower New ZealandLtd -- Neutron Monitor Network in Real Time and Space Weather -- Space Weather Research and the US Air Force Office of Scientific Research (AFOSR).
Keywords: PHYSICS; ASTROPHYSICS; PARTICLE ACCELERATION; ENVIRONMENTAL PROTECTION; PHYSICS; ELECTRICAL POWER GENERATION AND TRANSMISSION; EFFECTS OF RADIATION/RADIATION PROTECTION; NONLINEAR DYNAMICS, COMPLEX SYSTEMS, CHAOS, NEURAL NETWORKS; EXTRATERRESTRIAL PHYSICS, SPACE SCIENCES; PARTICLE ACCELERATION AND DETECTION, BEAM PHYSICS